Memorability of photographs in subjective cognitive decline and mild cognitive impairment: Implications for cognitive assessment. Issue 1 (1st December 2019) - Bainbridge, Wilma A.; Berron, David; Schütze, Hartmut; Cardenas‐Blanco, Arturo; Metzger, Coraline; Dobisch, Laura; Bittner, Daniel; Glanz, Wenzel; Spottke, Annika; Rudolph, Janna; Brosseron, Frederic; Buerger, Katharina; et al.
Abstract: Introduction: Impaired long‐term memory is a defining feature of mild cognitive impairment (MCI). We tested whether this impairment is item specific, limited to some memoranda, whereas some remain consistently memorable. Methods: We conducted item‐based analyses of long‐term visual recognition memory. Three hundred ninety‐four participants (healthy controls, subjective cognitive decline [SCD], and MCI) in the multicentric DZNE‐Longitudinal Cognitive Impairment and Dementia Study (DELCODE) were tested with images from a pool of 835 photographs. Results: We observed consistent memorability for images in healthy controls, SCD, and MCI, predictable by a neural network trained on another healthy sample. Looking at memorability differences between groups, we identified images that could successfully categorize group membership with higher success and a substantial image reduction than the original image set. Discussion: Individuals with SCD and MCI show consistent memorability for specific items, while other items show significant diagnosticity. Certain stimulus features could optimize diagnostic assessment, while others could support memory.